A numerical investigation of the effect of surface wettability on the boiling curve - Hsu, Hua-Yi; Lin, Ming-Chieh; Popovic, Bridget; Lin, Chii-Ruey; Patankar, Neelesh A. (PloS one, 2017)
Surface wettability is recognized as playing an important role in pool boiling and the corresponding heat transfer curve. In this work, a systematic study of pool boiling heat transfer on smooth surfaces of varying wettability (contact angle range of 5° - 180°) has been conducted and reported. Based on numerical simulations, boiling curves are calculated and boiling dynamics in each regime are studied using a volume-of-fluid method with contact angle model. The calculated trends in critical heat flux and Leidenfrost point as functions of surface wettability are obtained and compared with prior experimental and theoretical predictions, giving good agreement. For the first time, the effect of contact angle on the complete boiling curve is shown. It is demonstrated that the simulation methodology can be used for studying pool boiling and related dynamics and providing more physical insights.